The Role of TV Reality Show in Contributing to Changes in People’s Behaviour: A Phenomenological Approach - Mayagita, Avradya (Technium Social Sciences Journal, 2021)
This research is intended to dig deeper into what types of reality shows are currently being broadcast on television in Indonesia and how TV reality shows contribute to changes in people’s behaviour. This study uses a qualitative methodology with a phenomenological approach. For data collection, a semi-structured interview and observation are employed. Interviews were conducted with housewives who felt the changes in their children’s attitudes and behaviour after watching reality shows on television. Interviews were also conducted with teachers, psychologists and TV reality show producers. The results of this study proved that reality shows on Indonesian television make a major contribution to changing a person’s behaviour. This behavioural change can be positive or negative. Therefore, these reality shows require tighter control by the government through the Ministry of Communication and Information and Indonesia Broadcasting Commission (KPI).